Filter paper inhibits in vitro protocorm-like body formation in hybrid Cymbidium and reduces synseed germination, but buffers the negative impact of antibiotics - TEIXEIRA DA SILVA, JAIME A. (Biological Letters, 2015)
Only few studies in the plant tissue culture literature have examined the impact of filter paper on in vitro plant organogenesis. In this study, using a model plant, hybrid Cymbidium Twilight Moon ‘Day Light’, the impact of a single or double layer of Advantec #2 or Whatman #1 filter paper on new protocorm-like body (neo-PLB) formation on Teixeira Cymbidium (TC) medium was examined for half-PLBs (transgenic and non-transgenic), PLB-derived transverse thin cell layers (tTCLs), and PLB synseeds. In addition, the response of half-PLBs or tTCLs to two antibiotics (kanamycin and cefotaxime, commonly used in plant genetic transformation studies) was investigated either directly on gelled medium or on filter paper-overlaid medium. Filter paper negatively affected most growth and developmental parameters of all the explants tested, both transgenic and non-transgenic. A double sheet of filter paper had a significantly (P ≤ 0.05) more negative impact than a single sheet, relative to the control values (i.e., no filter paper). Kanamycin inhibited neo-PLB formation on TC medium, the negative impact being greater on a single layer than on a double layer of filter paper, i.e., filter paper buffered the growth-inhibiting characteristics of kanamycin. Up to 100 mg/l, cefotaxime showed no apparent negative effects on neo-PLBs formation and growth, although hyperhydricity was observed when filter paper was not used.